This is Not an Atlas. A Global Collection of Counter-Cartographies. - Kollektiv, Orangotango; Bertolini, Carolina; Bloom, Brett; Dayrit, Cian; Fisher, Ina; Hagen, Erica; Halder, Severin; Hirschmann, Anna; Irving, Adele; Lambio, Christoph; Mesquita, André; Michel, Boris; et al. (Bielefeld : transcript Verlag, 2018)
The Anti-Eviction Mapping Project ; The EJAtlas ; The Counter-Cartograhies Collective ; Geoide en Revolucion ; Hyderabad Urban Lab ; Iconoclasistas ; Imaginado Buenas ; mapping.postkolonial.net ; Kartographische Aktion ; Projeto Nova Cartografia Social da Amazonia ; Pappsatt ; The Working Group Critical Geographies of Global Inequalities (CGGI) ; 596 Acres ; Iconoclasistas ; Hyderabad Urban lab (HUL) ; HarassMap
cartografie, politieke strijd van minderheidsgroepen gevat in een atlas, mapping
boek
Keywords: Kollektiv Orangotango